Pengelolaan Program Pendidikan Madrasah Aliyah Negeri Insan Cendekia: Studi Kasus di MAN IC Sorong - Mohsen, Mohsen; Siregar, Imran; Ahmad, Abdul Kadir (Badan Litbang dan Diklat Kementerian Agama RI, 2023)
This research aims to describe the educational management of MAN IC Sorong as a superior madrasa that the supporting community can be proud of, with the hope that the results can be used as input in improving the quality of its management towards equality with the quality of the previous MAN IC. The result is that MAN IC Sorong needs a breakthrough to achieve the five advantages that were the main targets of its establishment. Efforts are needed to achieve this, through increasing commitment to developing curriculum and learning towards quality standards above national education standards, emphasizing the choice of local excellence typical of MAN IC Sorong, improving information and communication technology-based learning management, showing more of a spirit of excellence in daily activities such as which is ordered by MAN IC's vision, maximizing the use of available learning facilities, improving dormitory management to be more professional, and improving the daily process of mastering English and Arabic in the madrasah community. That is why strengthening management, especially in the aspect of developing collaborative networks with various related parties, is a priority for improvement as well as ensuring that native West Papuan students receive special quota allocations as an answer to the doubts of the local community and government in supporting the existence of superior Madrasahs in the Papua region.